1995
DOI: 10.1073/pnas.92.20.9368
|View full text |Cite
|
Sign up to set email alerts
|

Expression of human beta-amyloid peptide in transgenic Caenorhabditis elegans.

Abstract: Transgenic Caenorhabditis elegans nematodes have been engineered to express potentially amyloidic human proteins. These animals contain constructs in which the muscle-specific unc-54 promoter/enhancer of C. elegans drives the expression of the appropriate coding regions derived from human cDNA clones. Animals containing constructs expressing the 42-amino acid f3-amyloid peptide (derived from human amyloid precursor protein cDNA) produce muscle-specific deposits immunoreactive with anti-,3-amyloid polyclonal an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
511
0
5

Year Published

2000
2000
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 621 publications
(542 citation statements)
references
References 40 publications
10
511
0
5
Order By: Relevance
“…Several transgenic C. elegans lines have been successfully established to study human neurodegenerative disorders (35)(36)(37)(38)(39)(40). Such heterologous genetic models have proven to be very useful for understanding disease pathogenesis and developing therapeutic strategy.…”
Section: Discussionmentioning
confidence: 99%
“…Several transgenic C. elegans lines have been successfully established to study human neurodegenerative disorders (35)(36)(37)(38)(39)(40). Such heterologous genetic models have proven to be very useful for understanding disease pathogenesis and developing therapeutic strategy.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, the endocytosis-related genes we originally identified in our yeast screen, which are also known AD risk factors in humans, suppress Aβ toxicity in this nematode model (8). Expressing Aβ in glutamatergic neurons enables a quantitative measure of neurodegeneration and differs from previous approaches in the nematode where Aβ expressed within the body wall muscle cells caused a motor phenotype (24,25). As previously described, the percentage of worms with the WT number of neurons decreased from 3 to 7 d post larval hatching [ Fig.…”
Section: Screen For Compounds That Rescue Aβ Toxicity In Yeastmentioning
confidence: 99%
“…In vivo experiments were also performed in order to investigate the protective effect of TTR. In Caenorhabditis elegans expressing human A-Beta (1-42), TTR rescued the neurodegeneration triggered by the toxic peptide [13]. Studies in transgenic mice overexpressing mutant APP revealed slow disease progression and lack of neurodegeneration attributed to TTR expression [7].…”
Section: Introductionmentioning
confidence: 99%